Lepidópteros e seus parasitoides em cultura de quiabo em Ribeirão Preto, SP, Brasil - Lara, Rogéria Inês Rosa; Spera, Bruno Rafael; Versuti, Danielle Roberta; Fernandes, Daniell Rodrigo Rodrigues [UNESP]; Santos-Cividanes, Terezinha Monteiro; Perioto, Nelson Wanderley [UNESP] (FapUNIFESP (SciELO), 2012)
The aim of this study was to identify the defoliating lepidopterans and their parasitoids occurring on okra plants in the district of Riberão Preto city (SP. Brazil). Caterpillars were collected by hand from an experimental field of okra, in March and April, 2009. They were placed individually on Petri dishes lined with wet filter paper, containing shredded okra leaves, and kept in a climactic chamber (25±1°C, 12:12h light/ dark photoperiod, RH 70±10%) until the emergence of lepidopterans and/or parasitoids. In all, 63 lepidopterans were obtained: three species of Noctuidae, Anomis flava (Fabricius), Spodoptera frugiperda (Smith) and Pseudoplusia includens (Walker); one of Pieridae, Ascia monuste orseis (Godart), and an unidentified species of Tortricidae. One unidentified tachinid fly (Diptera) and the Hymenoptera parasitoids Copidosoma floridanum (Ashmead) (Encyrtidae) and Euplectrus sp. (Eulophidae) emerged from A. flava, while C. floridanum and an unidentified tachinid, from P. includens. This is the first report of an association between the herbivores S. frugiperda, P. includens and A. monuste orceis, the parasitoids C. floridanum and Euplectrus sp. on okra plants.
Lepidopterans and their parasitoids on okra plants in Riberão Preto (SP, Brazil)
Keywords: Abelmoschus esculentus; Copidosoma floridanum; Euplectrus; Parasitic hymenoptera; Tachinidae